(3ebGHS GdCfhGQ hfaGFS GdCSQGQ aj CMcGe GdfHj GdeNJGQ hYJQJg GdCWgGQs - (3GdcGXej, GdORahdj, CSO Gddg Hf ESeGYjd, J (B1220(3g`s
(3ChdgG (B:s
(3fMeOc jG ef CHdL HebGHS CfhGQ gOGjJg TQGFY GdESdGe (B... (3hHYO ajbhd GdeYJUe HMHd Gddg(B...(3CSO Gddg(B...(3gPG eG GTJOJ Edjg GdCThGb(B...(3ef JMQjQ cJG aGFb aj HjGf CegGJ GdCMcGe(B...s
(3BNQgG (B:s
(3hCjVG JOd gPg GdYHGQGJ hZjQgG Ydi Cf GdUHj EPG GQJVY aj Mhdjg(B...s
(3JHUQI GdeDda (B:s
(3CQN dhaGJg aj GdPQjYI HSfI (B1237(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B:(3L(B1(3U(B203s
(3GdPQjYI(B:(3L(B21(3,U(B241(3,Qbe(B5535s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis